Context of instauration and evolution under isavuconazole, a 2-year prospective real-life study. (24th March 2023) - Pieragostini, Rémi; Xhaard, Aliénor; Sauvageon, Hélène; Madelaine, Isabelle; Touratier, Sophie; Denis, Blandine
Abstract: To describe reasons for initiation and evolution under isavuconazole (ISZ), a 2-year prospective and observational study was performed. Anonymized data collected during the first 3 months of treatment were indications of treatment, efficacy, overall survival (OS), evolution of toxicity markers, and ISZ trough levels. Fifty-one (26 invasive aspergillosis, 16 prophylaxis, and 9 mucormycosis) patients started on isavuconazole. Isavuconazole was initiated upfront in 12/51 cases, especially to avoid toxicities from other antifungals. As second-line therapy (39/51 patients), isavuconazole was mostly initiated after toxicities of the previous treatments (66.7%; 26/39 cases). An improvement in toxicity markers was reported in most patients. However, five patients experienced adverse events. The mean ISZ trough levels measured from 179 samples collected in 37 patients was 3.33 ± 1.64 mg/l. The mean ISZ through levels was significantly lower ( P = .003) in alloHSCT recipients (3.10 ± 1.45 mg/l) than in other patients (3.76 ± 1.88 mg/l) but still within the expected range of efficacy. After 12 weeks, the OS was 69.2% ( n = 18/26) in the invasive aspergillosis intention-to-treat (ITT) group and 44.4% ( n = 4/9) in the mucormycosis ITT group. After 2 years, the OS was respectively 46.2% ( n = 12/26) and 33.3% ( n = 3/9) in these two groups. Lay Summary: Isavuconazole is commonly prescribed as second-line therapy after the toxicity of a previous treatment. In most cases, an improvement is reported. The well tolerability of isavuconazole was associated with correct blood levels, even in alloHSCT recipients.